2019
DOI: 10.1002/biot.201900013
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome and Flux Profiling of Crabtree‐Negative Hydroxy Acid‐Producing Strains of Saccharomyces cerevisiae Reveals Changes in the Central Carbon Metabolism

Abstract: Saccharomyces cerevisiae (S. cerevisiae) is the yeast cell factory of choice for the production of many biobased chemicals. However, it is a Crabtree‐positive yeast and so shuttles a large portion of carbon into ethanol. Ethanol formation can be eliminated by deleting pyruvate decarboxylase (PDC) activity. It is not yet well understood how PDC‐negative yeasts are affected when engineered to produce other products than ethanol. In this study, pathways are introduced for the production of three hydroxy acids (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Further research has demonstrated that flux through the PPP is correlated with biomass yields from glucose, with Crabtree-positive yeasts that produce fermentation products having a lower PPP flux than Crabtree-negative yeasts ( Blank et al, 2005 ). Preventing ethanol formation in S. cerevisiae may have led to 90% of the carbon uptake flux being diverted to the PPP ( Jessop-Fabre et al, 2019 ), although the authors noted experimental discrepancies in other studies. L. starkeyi produces relatively limited amounts of byproducts and has higher lipid yields than Y. lipolytica , which often secretes high amounts of organic acids ( Erian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research has demonstrated that flux through the PPP is correlated with biomass yields from glucose, with Crabtree-positive yeasts that produce fermentation products having a lower PPP flux than Crabtree-negative yeasts ( Blank et al, 2005 ). Preventing ethanol formation in S. cerevisiae may have led to 90% of the carbon uptake flux being diverted to the PPP ( Jessop-Fabre et al, 2019 ), although the authors noted experimental discrepancies in other studies. L. starkeyi produces relatively limited amounts of byproducts and has higher lipid yields than Y. lipolytica , which often secretes high amounts of organic acids ( Erian et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%